STUDIES ON THE FECUNDITY OF SETIPINNA TATY (VALENCIENNES) AND TRICHIURUS PANTULUI GUPTA OF THE HOOGHLY ESTUAR1NE SYSTEM - De, D K; Mitra, P M (Indian Journal of Fisheries, 2011)
Fecundity study on Setipinna taty (Vatenctanes') and Trichiurus pantuluiGupta of the Hoogly Esitoarime System has shown that the weight is the bestpredictor vanalbfe for estimating fecundity of 5. taty, whereas, for T. pantuluitotal weight db the best. The estimating equations are worked out as Xj = 877.95+1.897X2 for 5. taty and Xi = -1210.05'+57.&S6X4 for T. pantului, where X!is fecundity in number, X2 is tihe gonad weight in mg aind X4 iÂ» the total weightin mg.